The Le Comportement de Personnage Principal dans Le Roman Le Bleu Du Ciel de Georges Bataille Selon la Théorie de la Typologie Biologique de Hans Eysenck (Universitas Negeri Semarang, 2022)
This research aims to explain the extraversion, neuroticism and psychoticism of Troppman's character in the novel Le Bleu du Ciel using Hans Eysenck's Personality Dimensions theory. Personality dimensions include extraversion, neuroticism, and psychoticism. The material object of this research is the novel Le Bleu du Ciel by Georges Bataille. While the formal object is Dimensions of Personality by Hans Eysenck. The primary data source are the novel Le Bleu du Ciel by Georges Bataille and the Biological Typology theory by Hans Eysenck. Then, secondary data comes from articles and various sources related to the research issue. The method used is that of the analytical description Through analysis, the researcher concluded that Troppman is someone with a balanced level of extraversion and introversion, a high level of neuroticism, and a balanced level of psychoticism and superego. The higher the stress level, the more indicative of psychological disorders, such as Troppman experiencing serious illness, fond of hallucinations, and depression which causes the desire to end his life. The main cause, when he learned of his sexual disorder and the decision to separate from his wife. This made him an alcoholic and enjoyed having sex with prostitutes. The results of this research will be able to give a new idea to the students of the languages ​​and foreign literature in particular those of the French literature to understand and use the theory of the Biological Typology of Hans Eysenck